Analisis Terhadap Putusan Bebas dalam Kasus Tindak Pidana Korupsi Pengadaan Dana Anggaran Pendapatan dan Belanja Daerah (APBD) Kabupaten Pandeglang Banten - Annisa Ghitha Ashila Mulyadi (UNISBA Press, 2022)
The crime of corruption has become an extraordinary international crime (extra ordinary crime), as well as in efforts to eradicate it. Based on this phenomenon, the purpose of this study is to find out the basis for the judge's considerations and how legal remedies can be taken in the acquittal decision Number: 310/Pid.B/2009/PN.Pdg in the corruption crime of procuring funds from the Regency Regional Revenue and Expenditure Budget (APBD). Pandeglang Banten. The approach method used by the author is a normative legal approach or literature, that is, with reference to legal norms and legislatison related to this research, namely Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. , and using descriptive legal research specifications. The data collection technique used is secondary data with primary legal materials and secondary legal materials. Analysis of the data used is the analysis of library research (Library Research). Legal remedies that can be taken against a verdict free from all lawsuits (vrijspraak) at the level of examination of the district court or high court are ordinary legal remedies for cassation and extraordinary legal remedies for cassation for legal purposes. The judge's consideration in giving the verdict is free from all lawsuits (Vrijspraak), because there is a justification based on all the statements of witnesses and the confession of the Defendant at trial. The Panel of Judges acquitted the Defendant of all charges (Vrijspraak), and stated that the appeal for cassation could not be accepted. The Defendant was not proven to have violated Article 3 jo. Article 18 (1) letter b of Law no. 31 of 1999 concerning the Eradication of Corruption Crimes jo. Law No. 20 of 2001 concerning Amendments to Law no. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption in conjunction with Article 55 paragraph (1) of the 1st Criminal Code. Tindak Pidana Korupsi telah menjadi suatu kejahatan Internasional yang luar biasa (extra ordinary crime), begitu pula dalam upaya pemberantasannya. Berdasarkan fenomena tersebut, tujuan penelitian ini untuk mengetahui dasar pertimbangan hakim dan bagaimana upaya hukum yang dapat ditempuh dalam putusan bebas perkara Nomor : d310/Pid.B/2009/PN.Pdg alam Tindak Pidana Korupsi pengadaan Dana Anggran Pendapatan Belanja Daerah (APBD) Kabupaten Pandeglang Banten. Metode pendekatan yang digunakan penulis adalah metode penekatan hukum normatif atau kepustakaan yaitu, dengan mengacu pada norma-norma hukum serta peraturan perundang-undangan yang berhubungan dengan penelitian ini yaitu Undang-Undang Nomor 31 Tahun 1999 jo UU Nomor 20 Tahun 2001 Tentang Pemberantasan tindak Pidana Korupsi, serta menggunakan spesifikasi penelitian hukum penelitian hukum deskriptif. Teknik pengumpulan data yang digunakan adalah data sekunder dengan bahan hukum primer dan bahan hukum sekunder. Analisis data dipakai adalah analisis studi kepustakaan (Library Research). Upaya hukum yang dapat dilakukan terhadap putusan bebas dari segala tuntutan hukum (vrijspraak) pada tingkat pemeriksaan pengadilan negri atau pengadilan tinggi dalah upaya hukum biasa kasasi dan upaya hukum luar biasa kasasi demi kepentingan hukum. Pertimbangan hakim dalam memberikan putusan bebas dari segala tuntutan hukum (Vrijspraak), dikarenakan adanya alasan pembenar yakni berdasarkan semua keterangan saksi-saksi dan pengakuan Terdakwa di persidangan. Majlis Hakim membebaskan Terdakwa dari seluruh dakwaan (Vrijspraak), dan menyatakan tidak dapat diterima permohonan kasasi, Terdakwa tidak terbukti melanggar Pasal 3 jo. Pasal 18 (1) huruf b Undang-Undang No. 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi jo. Undang-Undang No. 20 Tahun 2001 tentang Perubahan atas Undang-undang No. 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi jo Pasal 55 ayat (1) ke-1 KUHP.